2020
DOI: 10.3847/1538-4357/ab80bd
|View full text |Cite
|
Sign up to set email alerts
|

What Constraints on the Neutron Star Maximum Mass Can One Pose from GW170817 Observations?

Abstract: The post-merger product of the first binary neutron star merger event detected in gravitational waves, GW170817, depends on neutron star equation of state (EoS) and is not well determined. We generally discuss the constraints one may pose on the maximum mass of a non-spinning neutron star, M TOV , based on the observations and some EoS-independent universal relations of rapidly-spinning neutron stars. If the merger product is a black hole after a brief hypermassive neutron star (HMNS) phase, we derive M TOV < … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 78 publications
2
57
0
Order By: Relevance
“…Energetic arguments suggest that the remnant star formed after the merger was initially a hypermassive neutron star which eventually collapsed into a black hole [284], though counterarguments also exist [285][286][287]. A number of studies have used this and different assumptions about the post-merger evolution of the system to suggest an upper limit on the maximum mass of stable, nonrotating neutron stars of 2.3M [201,284,[287][288][289][290][291][292]. Using a similar interpretation, a relation between the radius, the maximum neutron star mass, and the threshold mass for prompt collapse of the merger remnant [293] suggests R 1.6 10.6km [220].…”
Section: Multimessenger Constraintsmentioning
confidence: 99%
“…Energetic arguments suggest that the remnant star formed after the merger was initially a hypermassive neutron star which eventually collapsed into a black hole [284], though counterarguments also exist [285][286][287]. A number of studies have used this and different assumptions about the post-merger evolution of the system to suggest an upper limit on the maximum mass of stable, nonrotating neutron stars of 2.3M [201,284,[287][288][289][290][291][292]. Using a similar interpretation, a relation between the radius, the maximum neutron star mass, and the threshold mass for prompt collapse of the merger remnant [293] suggests R 1.6 10.6km [220].…”
Section: Multimessenger Constraintsmentioning
confidence: 99%
“…That information, together with gravitational-wave observations elucidating the nature of the remnant (e.g., Shibata et al 2019) and time it takes for the remnant to collapse to a black hole (Lucca & Sagunski 2020;Easter, Lasky, & Casey 2020), will be as important to our understanding of gamma-ray burst physics as the first multimessenger gravitational-wave observation GW170817/GRB170817A. The precise nature of the remnant of GW170817 is not known (e.g., Ai, Gao, & Zhang 2020), in large part due to the non-detection of post-merger gravitational waves (Abbott et al 2017f;2019c). The joint electromagnetic and gravitational-wave detection of GW170817-like events with the addition of a NEMO will enable significant further insight into gamma-ray burst physics.…”
Section: Other Sciencementioning
confidence: 99%
“…The lack of detection of such features suggests that the merger product of GW170817 may not be an SMNS. However, we note that the data for GW170817 suggest an M TOV ≤ 2.17 M if the newly formed remnant has been a short-lived HMNS (Margalit & Metzger 2017;Rezzolla et al 2018;Ai et al 2020), while in order to account for X-ray plateaus, M TOV would need to be relatively high, M TOV ∼ 2.3 M (Fan et al 2013a;Gao et al 2016). This difference may be reduced if the remnant formed in GW170817 had quickly or effectively lost its angular momentum through the GW radiation, for which M TOV ≤ 2.3 M is allowed for the general cases (Shibata et al 2019;Shao et al 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 77%
“…Fan et al (2020) showed that the properties of the binary NSs involved in GW170817 are in favor of strong post-merger GW radiation. In addition, as discussed in Ai et al (2020), the merger remnant of GW170817 may also have been a long-lived massive NS or even a stable NS. This question needs further investigation.…”
Section: Conclusion and Discussionmentioning
confidence: 99%